1996
DOI: 10.1007/bf02337544
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary histories of highly repeated DNA families among the artiodactyla (mammalia)

Abstract: Six highly repeated DNA families were analyzed using Southern blotting and fluorescence in situ hybridization in a comparative study of 46 species of artiodactyls belonging to seven of the eight extant taxonomic families. Two of the repeats, the dispersed bovine-Pst family and the localized 1.715 component, were found to have the broadest taxonomic distributions, being present in all pecoran ruminants (Giraffidae, Cervidae, Antilocapridae, and Bovidae), indicating that these repeats may be 25-40 million years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 44 publications
6
45
3
Order By: Relevance
“…The 1.715 satellite from B. taurus and the 1.714 satellite from O. aries proved to be informative markers (Modi et al 1996;Chaves et al 2000a) for studying the nature and amplification of the satellite DNA families on the autosomes and the X chromosome of the Bovidae family (figures 1,2,4 and 5; table 1) and allowed phylogeny to be inferred. Where we investigated several genera within a tribe, hybridization patterns were similar with the exception of the biarmed chromosomes, where satellite DNA reshuffling occurs (Chaves et al 2000b(Chaves et al , 2003b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1.715 satellite from B. taurus and the 1.714 satellite from O. aries proved to be informative markers (Modi et al 1996;Chaves et al 2000a) for studying the nature and amplification of the satellite DNA families on the autosomes and the X chromosome of the Bovidae family (figures 1,2,4 and 5; table 1) and allowed phylogeny to be inferred. Where we investigated several genera within a tribe, hybridization patterns were similar with the exception of the biarmed chromosomes, where satellite DNA reshuffling occurs (Chaves et al 2000b(Chaves et al , 2003b.…”
Section: Discussionmentioning
confidence: 99%
“…Sika (Cervus nippon) and white-tailed deer (Odocoileus virginianus) in the Cervidae family also carry 1.715-like satellite I sequences on the X chromosome (cited as unpublished observation by Gallagher et al (1999)) and these authors suggest that an acrocentric X chromosome with heterochromatin (and the 1.715 satellite I sequence) at the centromeres is the primitive condition. Modi et al (1996) hybridized a sequence representative of satellite I from Bos taurus (1.715 family) to different artiodactyl metaphases, and they found that this sequence was present in all pecoran animals analysed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jobse et al [16] studied the history of the Bov-B SINE elements by comparative hybridisation and PCR, and found that they emerged just after the diver-gence of the Camelidae and the true ruminants. Recently, Modi et al [17] used Southern blot hybridisation and fluorescent in situ hybridisation (FISH) to study the distribution of ART-2 retroposon in 46 species of artiodactyls, and found that it is specific for all pecoran ruminants (fam. Bovidae, Antilocapridae, Cervidae and Giraffidae).…”
mentioning
confidence: 99%
“…Szemraj proposed that the ART-2 retroposons should be considered as truncated BDDF (LINE-like) elements. Copy number estimates of ART-2 retroposon in the bovine genome range from 50000 [I41 to 200000 [17] copies/genome.…”
mentioning
confidence: 99%